2016
DOI: 10.1111/jar.12306
|View full text |Cite
|
Sign up to set email alerts
|

The Social‐Emotional Well‐Being of Children of Mothers with Intellectual Impairment: A Population‐Based Analysis

Abstract: Children of mothers with intellectual impairment are more likely than their peers to be exposed to adverse living conditions. These living conditions may explain, at least in part, why these children face a heightened risk of poor social-emotional well-being at ages 3 and 5. Improving the living conditions of mothers with intellectual impairment may offer a pathway to child social-emotional well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Without support, research has shown that the outcomes for children of parents with learning disabilities can be poor (Collings and Llewellyn 2012). Recent studies have shown the children of parents with learning disabilities to be at a heightened risk of poor social-emotional wellbeing and peer exclusion (Hindmarsh et al 2017); increased risk of injuries, violence and child abuse (Wickström et al 2017) and an increased risk of developmental delay and speech and language problems (Emerson and Brigham 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Without support, research has shown that the outcomes for children of parents with learning disabilities can be poor (Collings and Llewellyn 2012). Recent studies have shown the children of parents with learning disabilities to be at a heightened risk of poor social-emotional wellbeing and peer exclusion (Hindmarsh et al 2017); increased risk of injuries, violence and child abuse (Wickström et al 2017) and an increased risk of developmental delay and speech and language problems (Emerson and Brigham 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SEW relates to a child's self-perception and their ability to interact with others [5]. Children that experience SEW difficulties often demonstrate negative emotions and behaviours and struggle to maintain friendships [6]. In the long-term, SEW difficulties effect academic achievement and mental health in adulthood [7].…”
Section: Introductionmentioning
confidence: 99%
“…Research, ideally using population‐based data, is needed firstly to obtain robust, unbiased risk estimates, and secondly, to isolate the “effect” of parental intellectual disability, or rather the parenting practices of parents with intellectual disabilities, from the effects of adverse life conditions, including poverty and social isolation, on child health and development. In this special issue, Hindmarsh, Llewellyn, and Emerson analyse big data from the United Kingdom and find that children of mothers with intellectual impairment face a heightened risk of poor social‐emotional well‐being (at ages 3 and 5 years) and peer exclusion (by self‐report at age 7 years). However, the data also suggest that risk of poor child social‐emotional well‐being may diminish as child age increases, and may be explained by child exposure to environmental adversity, including household socioeconomic disadvantage.…”
Section: Children Of Parents With Intellectual Disabilitiesmentioning
confidence: 99%